Infant Deaths From Use of Crib Bumpers Are Increasing. Issue 4 (July 2016) - Beal, Judy A.
Abstract : Crib bumpers are still being widely used even though they have been found to cause infant deaths and injuries. Nurses can warn parents about crib bumper hazards and promote the "Bare is Best" campaign.